Experience of Fulfilling Nutritional Needs of Muslim Cervical Cancer Survivor: A Phenomenology Study - Distinarista, Hernandia; Wuriningsih, Apriliani Yulianti; Wahyuni, Sri; rahayu, Tutik (International Journal of Psychosocial Rehabilitation, 2020)
Cancer af ects all aspects of the patient’s life, both physically, psychologically and spiritually. Cancer does not always mean illness and suf ering for life. Patients who have recovered from cancer convey the opposite, namely health, wellbeing, and happiness after recovering from cancer. Complementary and alternative medicine (diet, herbs, supplements, therapies that involve the body, mind, and emotions) have an important role in helping people with cancer recover and prolong their lives. There are little data about how to meet the nutritional needs of cervical cancer patients, so this needs to be explored. Evidence-based information is needed by cancer patients to be able to live a quality life to the maximum and for a long time. The research aims to explore the experience of meeting the nutritional needs of cervical cancer survivors. The design of this study is qualitative with a hermeneutic phenomenology approach. An in-depth interview was conducted with five participants who were selected through purposive sampling. Data were analyzed using content analysis. Results: The results of this study obtained six themes, including (1) eating vegetables (2) eating fruit (3) avoiding MSG (4) avoiding foods containing preservatives (5) drinking a liquid that contains antioxidants, and (6) not consuming burnt foods. This study concludes that cancer survivors have positive and negative experiences in fulfilling nutritional needs while undergoing treatment for cervical cancer until healed. They prefer to consume healthy food without MSG and a lot of antioxidants.